Printing: its invention, progress and influence on education - Alexander, Mary E. (My University, 1902)
Introduction: a. Definition of printing. Printing, in its broadest sense, means “making an impression.” If this be accepted as a definition, we can trace its footprints to a period long before man stood upon the earth. Nature has printed the history of past ages on the very rocks that form the crust of the earth. Printing, as we take it, is, in reality typography, or the art of combining separate letters and taking from them an impression. b. Methods of keeping records before the invention of printing. Writing and block-printing. Before taking up the subjects of printing proper, it will be well to take a glance at the art of writing and that of block-printing. Although both differ widely from printing with movable type, yet this last process seems to have been such a gradual transition from block printing, and it, in its turn, such a natural outcome of the many trials to produce books in some more expeditious manner than could be done with hand-writing, that it will be well to study it a little.
Citation: Alexander, Mary E. Printing: its invention, progress and influence on education. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Printing; History of printing; Influence on education; Theses; Manuscripts (documents)